2022
DOI: 10.1136/tobaccocontrol-2021-057031
|View full text |Cite
|
Sign up to set email alerts
|

Public support for policies to regulate flavoured tobacco and e-cigarette products in rural California

Abstract: IntroductionFlavoured tobacco control policy exemptions and electronic cigarette products may contribute to increased youth access and tobacco use disparities.MethodsWe assessed public support among California Central Valley residents for four policies to regulate flavoured tobacco products and e-cigarettes. The probability-based, multimode survey was conducted with English-speaking and Spanish-speaking registered voters (n=845) across 11 counties between 13 and 18 August 2020. Weighted logistic regression ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Levy and colleagues 10 provide strong modelling support for the implementation of a ban on menthol in cigarettes and cigars in the USA, projecting it could prevent over 650 000 premature deaths and avert 11 million life-years lost over a 40-year window. Payán et al 11 showed majority support for flavoured product bans in a rural California sample. Meich and colleagues 12 show that within the USA, menthol cigarette use among adolescents is down substantially from 2012 to 2020, with the past 30 day use below 5% prevalence, even among Black adolescents, but suggest that bans could bring this down further.…”
Section: Flavoured Product Bans/restrictionsmentioning
confidence: 98%
“…Levy and colleagues 10 provide strong modelling support for the implementation of a ban on menthol in cigarettes and cigars in the USA, projecting it could prevent over 650 000 premature deaths and avert 11 million life-years lost over a 40-year window. Payán et al 11 showed majority support for flavoured product bans in a rural California sample. Meich and colleagues 12 show that within the USA, menthol cigarette use among adolescents is down substantially from 2012 to 2020, with the past 30 day use below 5% prevalence, even among Black adolescents, but suggest that bans could bring this down further.…”
Section: Flavoured Product Bans/restrictionsmentioning
confidence: 98%
“…A study suggests that no-smoking signs, when not supported by regulations, do not significantly impact smoking behaviour; therefore, installing no-smoking signs is crucial (Platter & Pokorny, 2018). Studies in several countries support tobacco restrictions and the placement of health warning signs due to smoking behaviour (Payán et al, 2022), and collaboration is considered strategically crucial for policy influence (Ikegwuonu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%